Transcriptomic and metabolomic analyses of three Dendranthema morifolium “Boju” varieties with different flower colors - Chen, Na; Liu, Kai; Li, Gang; Liu, Rui; Meng, Xiao; Zhang, Wanqiu; Guo, Xuanxuan; Zhao, Li; Ye, Shengming; Zhang, Yulei; Liu, Yaowu; Xing, Shihai (Frontiers in Plant Science, 2026)
IntroductionThis study aimed to identify the specific genes, key metabolic pathways, and differential metabolites associated with flower color formation in Dendranthema morifolium “Boju” (hereinafter, referred to as “Boju”). These analyses were intended to elucidate the causes underlying different flower colors in “Boju” and provide a theoretical basis for optimal breeding of “Boju”.Methods“Boju” varieties with pink-white (FB group), yellow-white (HB group), and pure yellow flowers (CH group) were subjected to transcriptomic and metabolomic analyses to identify the differentially expressed genes (DEGs) and differential metabolites in these varieties.ResultsTranscriptomic analysis showed varying enrichment pathways of the DEGs in the three groups. The pathways with higher numbers of enriched genes in the FB vs. CH and FB vs. HB groups were the same, including protein processing in endoplasmic reticulum, plant–pathogen interaction, plant hormone signal transduction, and mitogen-activated protein kinase signal pathway. In the HB vs. CH group, among the four pathways with a larger number of DEGs, three were consistent with the previous two groups. In addition, the number of enriched genes in the starch and sucrose metabolism pathways was also relatively large in this group. Metabolomic analysis indicated that the differential metabolites in the varieties were primarily enriched in the isoflavonoid and flavonoid biosynthesis pathways. In the FB vs. CH, FB vs. HB, and HB vs. CH groups, 28, 29, and 5 differential metabolites were enriched, with most of these metabolites enriched in either isoflavonoid or flavonoid biosynthesis pathways. These findings, combined with real-time quantitative polymerase chain reaction analysis, revealed a significant distribution of the flavonoid synthesis pathway, exceeding the significance threshold line. The differential expression of flavonoid metabolites and genes related to their biosynthetic pathways might primarily impact the formation of different flower colors in “Boju”.DiscussionTranscriptomic and metabolomic analyses indicated that the types and contents of anthocyanins varied across the “Boju” varieties, resulting in varying flower color. The key differential metabolites were primarily enriched in the isoflavonoid and flavonoid biosynthesis pathways. The DEGs in the different comparison groups exhibited varying enrichment in different pathways, but the enriched pathways were the same across the varieties.